2021
DOI: 10.20900/jpbs.20220008
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Function, and Genetics of the Cerebellum in Autism

Abstract: Autism spectrum disorders are common neurodevelopmental disorders that are defined by core behavioral symptoms but have diverse genetic and environmental risk factors. Despite its etiological heterogeneity, several unifying theories of autism have been proposed, including a central role for cerebellar dysfunction. The cerebellum follows a protracted course of development that culminates in an exquisitely crafted brain structure containing over half of the neurons in the entire brain densely packed into a highl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 125 publications
(127 reference statements)
0
2
0
Order By: Relevance
“…In addition, it plays a fundamental role in some cognitive functions such as emotional control, attention, language, and social behaviors. Several studies have shown that the cerebellum is structurally and functionally abnormal in autistic individuals (25): Individuals with CNTNAP2 mutations present with cerebellar malformations (26), and CNTNAP2 antibodies have been detected in the cerebrospinal fluid of subjects with mild cerebellar ataxia (27, 28). More recently, strong evidence has been obtained supporting the mechanistic contribution of cerebellar dysfunction to the pathogenesis of ASD-like behaviors in mouse models (29).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it plays a fundamental role in some cognitive functions such as emotional control, attention, language, and social behaviors. Several studies have shown that the cerebellum is structurally and functionally abnormal in autistic individuals (25): Individuals with CNTNAP2 mutations present with cerebellar malformations (26), and CNTNAP2 antibodies have been detected in the cerebrospinal fluid of subjects with mild cerebellar ataxia (27, 28). More recently, strong evidence has been obtained supporting the mechanistic contribution of cerebellar dysfunction to the pathogenesis of ASD-like behaviors in mouse models (29).…”
Section: Discussionmentioning
confidence: 99%
“…Among them, the heschl and superior frontal gyrus areas both play an important role in the classification based on two types of FC. We also find that both have a certain proportion in the cerebellum region [ 48 , 49 ]. Previous classification models or physiological studies also have some similar conclusions that differences exist in these brain areas [ 50 53 ].…”
Section: Resultsmentioning
confidence: 97%